Are “the semantic aspects” actually “irrelevant to the engineering problem”? - José María Díaz Nafría; Basil M. Al Hadithi (tripleC: Communication, Capitalism & Critique)
At the beginning of his famous “Mathematical Theory of Communication” (MTC), Shannon removes the semantic questions from the technical task, and such exoneration seems to be commonly accepted, even for those who certainly care for ‘semantic questions’. However, the MTC communication model itself is built upon this fundamental assumption, which at the same time is used in other information theories and –even with wider practical consequences– as a design pattern for the Information Technologies. When the human communication is more and more dependant with respect to information technologies, the suitability of the communication model used to design the technological systems has to be put into scope. Non essential element needed to establish a proper human communication should be omitted; otherwise this technology could isolate people, betraying its hypothetical purpose. Comparing the technological model to other based on several pragmatic theories of communication (emerged in linguistics, semiotic, psychology and anthropology) is shown the insufficiency of the technological model, pointing out some elements that a new model should not forget.